2019
DOI: 10.1177/0269215518819050
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of acupuncture for vascular cognitive impairment no dementia: a randomized controlled trial

Abstract: Objective: To evaluate the effectiveness of acupuncture in patients with vascular cognitive impairment no dementia (VCIND) in comparison with citicoline, an agent for cognitive disturbances associated with chronic cerebral disorders. Design: A randomized controlled multicenter trial. Setting: In three hospitals in Beijing, China. Subjects: A total of 216 patients with VCIND were recruited. Interventions: Patients with VCIND (mean age of 65.4 years) were randomized to receive acupuncture (two sessions p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Acupuncture has been reported to be a possible nonpharmacological treatment for VD patients. Our previous clinical trials suggested that acupuncture is useful in relieving symptoms of VD [42]. In this study, we found that acupuncture improved cognitive performance and reduced the levels of IL-6 and TNF-α in the hippocampus and plasma.…”
Section: Discussionsupporting
confidence: 57%
“…Acupuncture has been reported to be a possible nonpharmacological treatment for VD patients. Our previous clinical trials suggested that acupuncture is useful in relieving symptoms of VD [42]. In this study, we found that acupuncture improved cognitive performance and reduced the levels of IL-6 and TNF-α in the hippocampus and plasma.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies showed that acupuncture was effective for short-term improvement of cognitive function, but few reported the long-term effectiveness of acupuncture. Our findings on the effectiveness of acupuncture on the improvement of cognitive function are consistent with those of previously published clinical trials [ 24–26 ], while to date our trial is the only one characterized by a 6-month period of follow-up. Through a long follow-up period, we found that the effects of EA may last until 16 weeks after the beginning of intervention, and there were no differences between the two groups at 32 weeks of follow up.…”
Section: Discussionsupporting
confidence: 91%
“…Acupuncture therapy, a treatment modality of Chinese medicine, is widely recognized and used in many countries and regions in the world. At present, acupuncture therapy is applied for improving a variety of central nervous system diseases: dementia [ 19 , 20 ], stroke [ 21 , 22 ], Parkinson's disease [ 23 26 ], spinal cord injury [ 27 , 28 ], and so on [ 29 , 30 ]. Clinical research in AD found this therapy to be safe, well tolerated, and effective in improving cognitive function [ 10 ].…”
Section: Discussionmentioning
confidence: 99%